Preservation of digital literature: from stored to reinvented memory - Bouchardon, Serge (2013)
Regarding preservation, the digital age is the most fragile and complex context in the history of humanity. The added-value of digital technology is thus not where one expects. The digital medium is not a natural preservation medium, but digital technology makes us enter another universe which is a universe of reinvented and not stored memory. From this point of view, digital literature can be regarded as a good laboratory to address digital preservation: it makes it possible to raise the good questions and presents the digital age as a move from a model of stored memory to a model of reinvented memory.